Strategi Pengembangan Home Industry Era New Normal Pandemi Covid 19 Dalam Meningkatkan Pendapatan (Studi Kasus Kelompok Usaha Bersama (KUBE) â€œArjanjangâ€ Desa Selebung Ketangga, Kabupaten Lombok Timur) - Tati Atmayanti; Baiq Dewi Lita Andiana; Vici Handalusia Husni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
Community empowerment efforts through UMKM are a form of poverty eradication. One of them is by developing a home industry or home industry by forming a joint business group (KUBE). The Covid-19 pandemic has an impact on an economic downturn which has resulted in a decline in income and development of MSMEs, including in NTB. This study aims to formulate a home industry development strategy in the new normal era of the Covid-19 pandemic, in order to increase the income of KUBE "Arjanjang" in SELEBUNG KETANGGA Village, East Lombok. This study used a case study method with qualitative approach data collection techniques using questionnaires and interviews with the focus of research on KUBE "Arjanjang" which is engaged in the culinary field with technical analysis using SWOT analysis.The results of the study explain the home industry development strategy at KUBE "Arjanjang" in quadrant I position, namely the growth strategy is to improve the quality of processed banana flower production by utilizing the potential that can provide renewable innovation in production so as to create various flavors, improve the quality of adequate human resources so that they are able give a new touch to product appearance, such as packaging, promotion, use of digital media and have a reliable management (management) capability. In addition, to establish broader cooperation, both with banana farmers and other entrepreneurs and broaden the capital access through more financial institutions.   In facing the New Normal condition, KUBE "Arjanjang" as much as possible always adhere to health protocols, and of course make optimal use of government assistance.